Febuxostat improves outcome in a rat model of cancer cachexia. Issue 2 (21st April 2015) - Konishi, Masaaki; Pelgrim, Loes; Tschirner, Anika; Baumgarten, Anna; von Haehling, Stephan; Palus, Sandra; Doehner, Wolfram; Anker, Stefan D.; Springer, Jochen
Abstract: Background: Activity of xanthine oxidase is induced in cancer cachexia, and its inhibition by allopurinol or oxypurinol improves survival and reduces wasting in the Yoshida hepatoma cancer cachexia model. Here, we tested the effects of the second‐generation xanthine oxidase inhibitor febuxostat compared with placebo in the same model as used previously by our group. Methods: Wistar rats ( 200 g) were treated daily with febuxostat at 5 mg/kg/day or placebo via gavage for a maximum of 17 days. Weight change, quality of life, and body composition were analysed. After sacrifice, proteasome activity in the gastrocnemius muscle was measured. Muscle‐specific proteins involved in metabolism were analysed by western blotting. Results: Treatment of the tumour‐bearing rats with febuxostat led to a significantly improved survival compared with placebo (hazard ratio: 0.45, 95% confidence interval: 0.22–0.93, P = 0.03). Loss of body weight was reduced (−26.3 ± 12.4 g) compared with placebo (−50.2 ± 2.1 g, P < 0.01). Wasting of lean mass was attenuated (−12.7 ± 10.8 g) vs. placebo (−31.9 ± 2.1 g, P < 0.05). While we did not see an effect of febuxostat on proteasome activity at the end of the study, the pAkt/Akt ratio was improved by febuxostat (0.94 ± 0.09) vs. placebo (0.41 ± 0.05, P < 0.01), suggesting an increase in protein synthesis. Conclusions: Febuxostat attenuated cachexia progression and improved survival of tumour‐bearing rats.